Level of nickel in the Gibberulus gibberulus and in sediments in the intertidal area of Brgy. Buenavista, Manicani, Guiuan, Eastern Samar - Aurelia, Jake G.; Ricarte, Marjhun A. (2017)
Nickel is ubiquitous in the biosphere and ranks 24th in crustal abundance of all elements. Though nickel is an important economic metal, mining can create a potential source of heavy metal pollution in the aquatic environment thus it can lead to latent toxic responses in the affected organisms. In this study, samples of gastropod Gibberulus gibberrulus and sediments were obtained at two sites at the intertidal zone of Brgy. Buenavista in the island of Manicani, Eastern Samar. These were then analysed for nickel concentration and results showed that there was a greater nickel content level in residential area (15.66 plus or minus 0.79 ug/g; 4.97 plus or minus 0.17 ug/g) than in the mangrove area (9.31 plus or minus 0.33 ug/g; 4.48 plus or minus 0.14 ug/g) in both sediments and soft tissues of the gastropod, respectively. However, there was no significant differences between the two in both areas as revealed by two-tailed t-test. The mean concentration of nickel did not go above the National Oceanic and Atmospheric Administration Guidelines and the Threshold Effect Concentration (TEC) and Probable Effect Concentration (PEC) for sediments suggesting that no adverse biological effect is expected and that it is non-toxic in both areas. Gastropod nickel concentration was below the nickel limit set by Guangdong, China and calculated Estimated Dietary Intake (EDI) was below the Provisional Tolerable Daily Intake (PTDI) established by the joint FAO/WHO Expert Committee on Food Additives thus the gastropod is safe for consumption.
Research paper (B.S. Biology) -- University of the Philippines, Tacloban.